Inverted social reward: associations between psychopathic traits and self-report and experimental measures of social reward. - Lucy Foulkes (Public Library of Science (PLoS), 2014)
Individuals with high levels of psychopathic traits tend to undervalue long-term, affiliative relationships, but it remains unclear what motivates them to engage in social interactions at all. Their experience of social reward may provide an important clue. In Study 1 of this paper, a large sample of participants (N  =  505) completed a measure of psychopathic traits (Self-Report Psychopathy Scale Short-Form) and a measure of social reward value (Social Reward Questionnaire) to explore what aspects of social reward are associated with psychopathic traits. In Study 2 (N = 110), the same measures were administered to a new group of participants along with two experimental tasks investigating monetary and social reward value. Psychopathic traits were found to be positively correlated with the enjoyment of callous treatment of others and negatively associated with the enjoyment of positive social interactions. This indicates a pattern of 'inverted' social reward in which being cruel is enjoyable and being kind is not. Interpersonal psychopathic traits were also positively associated with the difference between mean reaction times (RTs) in the monetary and social experimental reward tasks; individuals with high levels of these traits responded comparatively faster to social than monetary reward. We speculate that this may be because social approval/admiration has particular value for these individuals, who have a tendency to use and manipulate others. Together, these studies provide evidence that the self-serving and cruel social behaviour seen in psychopathy may in part be explained by what these individuals find rewarding.